Algebraische Zahlentheorie: 27.3. bis 1.4.1978 - Jehne, Wolfram; Leopoldt, Heinrich-Wolfgang; Roquette, Peter (Tagungsbericht, 1978)
P. Báyer, Regensburg; E. Becker, Köln; H. Brunotte, Essen; V. Ennola, Turku; G. Frey, Saarbrücken; A. Fröhlich, London; W.-D. Geyer, Erlangen; G. Greiter, München; F. Halter-Koch, Essen; P. Henn, Saarbrücken; W. Henn, Karlsruhe; H. Jacobinski, Göteborg; W. Jehne, Köln; E. Kani, Heidelberg; J. Klingen, Köln; N. Klingen, Köln; J. Leicht, Heidelberg; H. W. Leopoldt, Karlsruhe; A. Leutbecher, München; G. Martens, Erlangen; B. H. Matzat, Karlsruhe; T. Metsänkylä, Turku; Y. Morita, Bonn; M. Neubrand, Bonn; J. Neukirch, Regensburg; R. Perlis, Bonn; H. P. Rehm, Karlsruhe; P. Roquette, Heidelberg; R. Schertz, Köln; C.-G. Schmidt, Saarbrücken; P. Schneider, Regensburg; H.-J. Stender, Köln; G. Tamme, Regensburg; R. Traniser, Heidelberg; W. Trinks, Karlsruhe